The Techniques Used In Teaching Writing Promote Student Efficiency, And The Use Of Direct Instruction By The Instructor Raises Efl Levels - Ibragimova Zarifa Nabiyevna, (European Journal of Life Safety and Stability (2660-9630), 2022)
The results of the study indicate that the graduating students adopted a critical theoretical framework and procedural/motor goals in their lesson plans. During the interventions, the participants prioritized the teaching of technical/motor content through global and analytical tasks; valued instruction strategies of explanation, demonstration, management interventions, and prescriptive and evaluative feedback; adopted management strategies, primarily group and individual strategies, emphasizing the restricted access of students to materials, and sought to establish a social relationship focused on themselves.